The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1080/21655979.2021.2006966
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the mechanism of luteolin against ischemic stroke based on network pharmacology, molecular docking and experimental verification

Abstract: Stroke is a leading cause of morbidity and mortality worldwide. As the most common type of stroke cases, treatment effectiveness is still limited despite intensive research. Recently, traditional Chinese medicine has attracted attention because of potential benefits for stroke treatment. Among these, luteolin, a natural plant flavonoid compound, offers neuroprotection following against ischemic stroke, although the specific mechanisms are unknown. Here we used network pharmacology, molecular docking, and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
(85 reference statements)
0
19
0
1
Order By: Relevance
“…It may have a therapeutic effect on stroke through TNF signaling. Rholin has been shown to combat ischemia and reperfusion injury, reducing the size of the infarcted area in experimental models [13] . Ursolic acid regulates TLR signaling and exhibits significant anti-inflammatory properties, which can reduce the production of inflammatory cytokines through the High Mobility Group Box 1 (HMGB1)/TLR4/Nuclear Factor Kappa B (NF-κB) signaling pathway to protect the brain from cerebral ischemia and reperfusion injury [14] .…”
Section: Resultsmentioning
confidence: 99%
“…It may have a therapeutic effect on stroke through TNF signaling. Rholin has been shown to combat ischemia and reperfusion injury, reducing the size of the infarcted area in experimental models [13] . Ursolic acid regulates TLR signaling and exhibits significant anti-inflammatory properties, which can reduce the production of inflammatory cytokines through the High Mobility Group Box 1 (HMGB1)/TLR4/Nuclear Factor Kappa B (NF-κB) signaling pathway to protect the brain from cerebral ischemia and reperfusion injury [14] .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is quite appropriate to adopt GSEA for investigating the possible pathways and potential targets of LUT for LOD treatment. Molecular docking simulations predict affinity and binding modes through ligand–receptor interactions, which helps to provide a reliable basis for experiment-based assays, thereby accelerating drug design and selection [ 35 ]. Consequently, mechanistic studies of LUT against LOD, based on proteomics, GSEA, and molecular docking to simulate natural compound–target binding, can provide a foundation for the development of targeted drugs for LOD.…”
Section: Discussionmentioning
confidence: 99%
“…In order to find the core genes of network, Cytoscape 3.9.1 software was used for PPI network diagram visualization. The node whose degree were greater than the average value were AKT1 (37), TNF (37), ALB (37), TP53 (36), VEGFA (36), IL6 (35), HIF1A (34),CASP3 (33), ESR1 (33), CAT (32), PTGS2 (32), HSP90AA1 (31), EGFR (30), MTOR (30), PTEN (30), HMOX1 (28), NOS3 (28), CASP8 (28), MMP9 (27), CASP9 (24), and SOD1 (23) (Fig. 3B), which may play an important role in the treatment of THSWD with varicocele-associated male infertility.…”
Section: Construction and Visualization Analysis Of The Ppi Networkmentioning
confidence: 99%
“…Luteolin is a kind of natural brass, and numerous studies have shown that it has anti-inflammatory, antioxidant, and anti-cancer biological activities. [31][32][33] Boeing et al [34] found that luteolin could reduce the oxidative stress response caused by iritantan by reducing reactive oxygen species and enhancing endogenous antioxidants. It also alleviated inflammation by reducing TNF, IL-1β and IL-6 levels and increasing IL-4 and IL-10 levels.…”
Section: Tablementioning
confidence: 99%